2000
DOI: 10.1021/jp000273g
|View full text |Cite
|
Sign up to set email alerts
|

Properties of the HCl/Ice, HBr/Ice, and H2O/Ice Interface at Stratospheric Temperatures (200 K) and Its Importance for Atmospheric Heterogeneous Reactions

Abstract: The properties of the interface region of bulk, vapor-deposited, and single-crystal ice have been studied in a Knudsen cell flow reactor in the range 190−210 K using repetitive pulse experiments (RPEs) at variable frequency. Fluxes of surface-to-bulk loss in ice on single-crystal and bulk ice vary from 5 × 1011 to 1 × 1013 and from 5 × 1012 to 5 × 1014 molecule s-1 cm-2 for HCl and D2O, respectively. A positive activation energy for diffusional loss of E A = 3.0 ± 0.5 kcal/mol for HCl/ice and 5.3 ± 0.7 kcal/mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
47
0

Year Published

2001
2001
2006
2006

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(55 citation statements)
references
References 45 publications
8
47
0
Order By: Relevance
“…Although n was similar in all experiments where overlayer formation was observed, the thickness varied between 10 and 100 nm for different P HCl and different ice crystals. This estimate is in agreement with a recent study showing that HCl is available on ice for reaction with ClONO 2 as deep as Ϸ100 nm (27)(28)(29). The measured index of refraction of Ϸ1.34 for the surface layer clearly exceeded that of ice, indicating that the observed transition was not a roughening transition.…”
Section: Resultssupporting
confidence: 91%
See 1 more Smart Citation
“…Although n was similar in all experiments where overlayer formation was observed, the thickness varied between 10 and 100 nm for different P HCl and different ice crystals. This estimate is in agreement with a recent study showing that HCl is available on ice for reaction with ClONO 2 as deep as Ϸ100 nm (27)(28)(29). The measured index of refraction of Ϸ1.34 for the surface layer clearly exceeded that of ice, indicating that the observed transition was not a roughening transition.…”
Section: Resultssupporting
confidence: 91%
“…The best agreement with our observations was obtained with a value of HCl solubility in the overlayer that was intermediate between that of a true liquid layer and that of bulk ice. We assumed an HCl-ice diffusion coefficient of 10 Ϫ12 cm 2 ⅐s Ϫ1 , which was measured by Thibert and Domine (35) for single crystals of ice at 258 K. This interpretation is consistent with those of Huthwelker et al (36) and Rossi and coworkers (27)(28)(29). Molecular-level details regarding uptake under nondisordered conditions, including the location of the adsorbed HCl and the state of the adsorbate, are currently unknown.…”
Section: Discussionsupporting
confidence: 62%
“…The diffusion constants of HCl in/on H 2 O ice, measured since the advent of recent PSC research, have varied from Dϳ10 Ϫ11 to 10 Ϫ4 cm 2 /s. 12,[27][28][29][30][31][32][33][34][35][36][37] There is considerable contention regarding the experiments on diffusion within thin ice films. 35,36 This has nevertheless been convincingly worked out by careful analysis of temperature dependence, thermodynamics, and, most importantly, the crucial role of ice sample morphology by Domine et al, 29,30,36 who favor a stratospheric value of Dϳ10 Ϫ17 cm 2 /s.…”
Section: Introductionmentioning
confidence: 99%
“…Recent laboratory work on coadsorption of HCl and HNO 3 on ice showed that HNO 3 acidified the ice surface and preferentially displaced HCl, suggesting that chlorine activation on cirrus particles may be substantially slowed when HNO 3 is in excess of HCl [ Hynes et al , 2002]. Fluckiger et al [2000] studied HCl diffusion in ice under UTLS conditions and showed that production of Cl 2 or HOCl depends on the size of the ice particle.…”
Section: Introductionmentioning
confidence: 99%